Gene delivery of albumin binding peptide‐interferon‐gamma fusion protein with improved pharmacokinetic properties and sustained biological activity. Issue 9 (5th March 2013) - Miyakawa, Noriko; Nishikawa, Makiya; Takahashi, Yuki; Ando, Mitsuru; Misaka, Masayuki; Watanabe, Yoshihiko; Takakura, Yoshinobu; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract We have demonstrated that gene delivery of a fusion protein of mouse interferon (IFN) γ with mouse serum albumin (IFNγ–MSA) was effective in prolonging the circulation half‐life of IFNγ in mice. However, the fusion to MSA greatly reduced the biological activity of IFNγ to less than 1%. In this study, we designed IFNγ fusion proteins with a 20 amino‐acid long albumin‐binding peptide (ABP) to prolong the in vivo half‐life of IFNγ without reducing its biological activity. IFNγ–ABP and ABP–IFNγ, two fusion proteins with the ABP being fused to the C‐ or N‐terminal of IFNγ, retained 40%–50% biological activities determined using a gamma‐activated sequence‐dependent luciferase assay. These fusion proteins exhibited the ability to bind to MSA. Gene delivery of IFNγ–ABP or ABP–IFNγ to mice using the hydrodynamic injection method resulted in a sustained concentration of IFNγ in the serum compared with gene delivery of IFNγ. In addition, the growth of mouse colon carcinoma CT‐26 cells in the lung was efficiently inhibited by gene delivery of the IFNγ fusion proteins. These results indicate that the fusion of ABP is a useful approach to achieving prolonged retention in the blood circulation through binding to serum albumin and retaining biological activity. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3110–3118, 2013